1991
DOI: 10.1007/bf02857820
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity and clinico-pathological effect ofAgave lophantha

Abstract: Dry powder and different extracts of Agave lophantha were tested against Biomphalaria alexandrina. The results showed that the butanol extract has high molluscicidal activity. The activity of the dry powder has been found to be stable under the effect of some simulated field conditions. Also the toxicological effect of the plant on mice was tested through determination of certain parameters such as total protein, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and acid phosphatase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Several articles had reported on different biological activities of the above species, namely, anti-inflammatory and molluscicidal properties of Agave americana (Shoeb et al, 1984;Peana et al, 1997), molluscicidal activity of Agave lophantha (El-Sayed et al, 1991), anti-inflammatory activity of Calotropis procera (Kumar & Basu, 1994), hypoglycemic activity of Pergularia tomentosa (Shabana et al, 1990), antiviral activity of Alkanna orientalis (El-Sohly et al, 1997), antibacterial, antinociceptive, and antiinflammatory effects of Pimenta racemosa Saenz et al, 2004), antimicrobial activities of Verbascum sinaiticum (Tadeg et al, 2005), molluscicidal properties of Solanum elaeagnifolium (Bekkouche et al, 2000), and molluscicidal and cercaricidal activities of Solanum nigrum (Ahmed & Ramzy, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Several articles had reported on different biological activities of the above species, namely, anti-inflammatory and molluscicidal properties of Agave americana (Shoeb et al, 1984;Peana et al, 1997), molluscicidal activity of Agave lophantha (El-Sayed et al, 1991), anti-inflammatory activity of Calotropis procera (Kumar & Basu, 1994), hypoglycemic activity of Pergularia tomentosa (Shabana et al, 1990), antiviral activity of Alkanna orientalis (El-Sohly et al, 1997), antibacterial, antinociceptive, and antiinflammatory effects of Pimenta racemosa Saenz et al, 2004), antimicrobial activities of Verbascum sinaiticum (Tadeg et al, 2005), molluscicidal properties of Solanum elaeagnifolium (Bekkouche et al, 2000), and molluscicidal and cercaricidal activities of Solanum nigrum (Ahmed & Ramzy, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…From the above, different research has found that some Agave species such as A. filifera, A. celsii, A. sisalana, A. decipiens Baker, and A. lophanta exerted molluscicide activity against Biomphalaria alexandrina [75,[89][90][91], a snail vector of Schistosoma mansoni, which causes schistosomiasis. The effective lethal dose and extract type are summarized in Table 3.…”
Section: Molluscicide Activitymentioning
confidence: 99%
“…The toxicity and rising costs of synthetic molluscicides have led to interest in compounds derived from locally growing plants that can be used as molluscicides. For example, extracts of Agave attenuata, Agave sislana, Agave igrelliana, Agave lophantha, Phytolaca dodecandra, Euphorbia spllendens and Ambrosisa maritima have been tested as molluscicide activity (De Souza et al, 1987;El-Sayed et al, 1991;Abdel-Hamide, 1997;Mendes et al, 1997;Brackenbury, 1999;Tiwari et al, 2004).…”
Section: Introductionmentioning
confidence: 97%